A comprehensive review on tyrosinase inhibitors - Samaneh Zolghadri; Asieh Bahrami; Mahmud Tareq Hassan Khan; J. Munoz-Munoz; F. Garcia-Molina; F. Garcia-Canovas; Ali Akbar Saboury (Taylor & Francis Group, 2019)
Tyrosinase is a multi-copper enzyme which is widely distributed in different organisms and plays an important role in the melanogenesis and enzymatic browning. Therefore, its inhibitors can be attractive in cosmetics and medicinal industries as depigmentation agents and also in food and agriculture industries as antibrowning compounds. For this purpose, many natural, semi-synthetic and synthetic inhibitors have been developed by different screening methods to date. This review has focused on the tyrosinase inhibitors discovered from all sources and biochemically characterised in the last four decades.